2017
DOI: 10.3390/nu9050452
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Levels Are Inversely Correlated with Body Weight and Obesity in an Elderly Population after 5 Years of Follow Up (The Randomised PREDIMED Study)

Abstract: Overweight and obesity have been steadily increasing in recent years and currently represent a serious threat to public health. Few human studies have investigated the relationship between polyphenol intake and body weight. Our aim was to assess the relationship between urinary polyphenol levels and body weight. A cross-sectional study was performed with 573 participants from the PREDIMED (Prevención con Dieta Mediterránea) trial (ISRCTN35739639). Total polyphenol levels were measured by a reliable biomarker, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 74 publications
4
40
0
1
Order By: Relevance
“…Obesity may impact pharmacokinetics of polyphenols by lowering absorption and metabolism, while increasing excretion . This may, in part, be due to altered polyphenolic transport and metabolism in the liver and colon .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity may impact pharmacokinetics of polyphenols by lowering absorption and metabolism, while increasing excretion . This may, in part, be due to altered polyphenolic transport and metabolism in the liver and colon .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, flavanones, flavones and lignans intake resulted in less notable increase in body mass index; flavanones, flavones, hydroxycinnamic acids, and lignans intake was associated to a less notable increase in waist circumference (Adriouch et al, ). A cross‐sectional study was performed with 573 participants at high cardiovascular risk; after 5‐year follow‐up, significant inverse correlation between total urinary polyphenol excretion and body weight, body mass index, waist circumference, and waist‐to‐height ratio was observed (Guo et al, )…”
Section: Polyphenol Intake and Human Healthmentioning
confidence: 99%
“…Hydroxybenzoic acids are known mainly due to their antioxidant properties with a potential in chronic diseases. Epidemiological studies have revealed inverse association between hydroxybenozoic acids intake and the risk of cardiovascular diseases and obesity (Guo et al, 2017;Tresserra-Rimbau et al, 2014a;Tresserra-Rimbau et al, 2014b).…”
Section: Phenolic Acids-hydroxycinnamic and Hydroxybenzoic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a prospective study with 807 participants over 65 years of age observed a 30% decreased mortality risk in individuals with higher total urinary polyphenol (Zamora‐Ros et al., ). In a cross‐sectional study of a cohort of older adults ( n = 573, 67.2 years old), at high CVD risk, a higher intake of polyphenol was inversely associated with body weight ( β = −1.004; 95% CI [−1.634, −0.375], p = .002) suggesting that it may be contributing factor to the body weight reduction in older adults (Guo et al., ).…”
Section: Functional Food Products For Older Individualsmentioning
confidence: 99%